2010
DOI: 10.2147/jmdh.s4743
|View full text |Cite
|
Sign up to set email alerts
|

Uses and benefits of omega-3 ethyl esters in patients with cardiovascular disease

Abstract: Much evidence on the favorable effects of omega-3 ethyl esters on cardiovascular morbidity and mortality has been obtained in studies performed in healthy subjects and in different clinical settings. Here the clinical effects of omega-3 ethyl ester administration in patients with previous myocardial infarction or heart failure are reviewed, together with a discussion of underlying mechanisms of action. The pharmacokinetic and pharmacodynamic properties of omega-3 ethyl esters, as well as evidence concerning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…This protection from the loss of coupling is likely to cause a decrease in the arrhythmogenic potential of the heart. This could explain why studies have shown that almost half the reduction of risk for people on w3 fatty acids supplementation was due to a decrease in arrhythmic events and Sudden Cardiac Death (Levantesi et al, 2010 ). These data suggest that early and consistent dietary supplementation with w3 fatty acids may limit cardiovascular risk overall when part of the normal diet prior to any cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…This protection from the loss of coupling is likely to cause a decrease in the arrhythmogenic potential of the heart. This could explain why studies have shown that almost half the reduction of risk for people on w3 fatty acids supplementation was due to a decrease in arrhythmic events and Sudden Cardiac Death (Levantesi et al, 2010 ). These data suggest that early and consistent dietary supplementation with w3 fatty acids may limit cardiovascular risk overall when part of the normal diet prior to any cardiac injury.…”
Section: Discussionmentioning
confidence: 99%